The absorption of ultrasonic waves in the mixtures of Kneser liquids - LINDE, B.B.J. (Archives of Acoustics, 1995)
Measurement of the absorption and velocity of ultrasonic waves in the mixtures of thiophene with m- and p-xylenes were made by Eggers method of the frequencies between 0.3 and 5 MHz and temperature 293 K and carbon tetrachloride with o-, m- and p-xylenes by pulse method in the frequency range 20-30 MHz. The absorption decreased with increasing the quantity of xylenes, as is predicted by theory for gases and these results suggest that the absorption is probably due to the same phenomenon as in the gases. In measured frequency range is any dispersion region.